2019
DOI: 10.28992/ijsam.v3i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Reporting on Financial Performance: Study of Global Fortune 500 Companies

Abstract: This study examines the impact of environmental reporting on the financial performance of Fortune 500 firms from 2013 to 2017. It appraises financial performance by measuring three independent variables: reduction in greenhouse gas emissions, reduction in waste, and reduction in water consumption. While the target population comprised the top 100 CSR-reputed companies listed on Fortune 500, the sample size was determined to be 50 based on observations of 250 companies. The collected data were analyzed using de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
9
2
Order By: Relevance
“…It is observed that there is an overestimated GDP traditional measure by 51-64%, which is the real economic income produced by Peruvian metal mining sector during the period 1992-1996. Cortez and Cudia (2011) explores the impact of environmental innovations on financial performance of Japanese electronics companies following the growing literature linking corporate social performance with profitability. The sample consists of 10 automotive and 10 electronic companies listed in the Tokyo Stock Exchange.…”
Section: Prior Empirical Evidence On Environmental Accounting (Ea) Anmentioning
confidence: 99%
“…It is observed that there is an overestimated GDP traditional measure by 51-64%, which is the real economic income produced by Peruvian metal mining sector during the period 1992-1996. Cortez and Cudia (2011) explores the impact of environmental innovations on financial performance of Japanese electronics companies following the growing literature linking corporate social performance with profitability. The sample consists of 10 automotive and 10 electronic companies listed in the Tokyo Stock Exchange.…”
Section: Prior Empirical Evidence On Environmental Accounting (Ea) Anmentioning
confidence: 99%
“…Green investment as a part of firms' sustainability drive has become a strategic issue in their decision making as ensuring economic success cannot be compromised (Lestari et al, 2019;Ong et al, 2020). Traditionally, environmental investments are considered a cost concerning activities incurring losses for firms; however, other argue that such actions are necessary to improve the relationship with stakeholders and to achieve profitability in the long run (Trumpp & Guenther, 2017;Zamil & Hassan, 2019). Regardless of the conflicting arguments, stakeholders have raised concerns regarding climate change and Indonesian Journal of Sustainability Accounting and Management, 2021, 5(1), [23][24][25][26][27][28][29][30][31][32] increasing carbon emission .…”
Section: Introductionmentioning
confidence: 99%
“…When companies can practice profitable business, they can be said to behave ethically (Zamil & Hassan, 2019). Disclosure of ethics and integrity in sustainability reporting can also increase its commitment to ethical behavior, especially relating to waste generated by the production process.…”
Section: Indonesian Journal Of Sustainabilitymentioning
confidence: 99%